Unexpected morphological changes within hippocampal structures in a photochemical ring model of cerebral ischaemia - Rafałowska, Janina; Gadamski, Roman; Dziewulska, Dorota; Zielonka, Piotr; Ogonowska, Wanda; Łazarewicz, Jerzy W. (Folia Neuropathologica, 2009)
A photochemical ring model of ischaemia was introduced in the middle of the nineteen eighties. Irradiation by a laser or arc lamp followed by intravenous injection of rose bengal resulted in thrombosis of pial and superficial cortical vessels. This ring model imitated focal ischaemic damage in humans. In our experiment twenty-seven Wistar rats of both sexes weighing 250-300 grams were examined. A photochemical ring model based on irradiation of the area of parietal bone 4 mm posteriorly to the bregma and 4 mm laterally from the sagittal suture was applied. A ring-shaped light beam with a wavelength of 510-540 nm with 5 mm diameter was generated by a high pressure discharge lamp at a power of 400 W. Two groups of rats treated and untreated with MK-801 and two rings of the thickness of 0.35 mm and 0.5 mm were used in the experiment. Morphological examination was performed in animals sacrificed 1 and 4 days after the irradiation. On formalin-fixed and paraffin-embedded slices HE staining method and immunoreaction with antibodies to ubiquitin were applied. Our material confirmed well known information about the dynamics of infarct breakdown, ischaemic-induced angiogenesis, glial reaction and other typical changes described previously in handbooks and numerous papers. In the experiment, morphological changes were more intensive after the irradiation by 0.5 mm than 0.35 mm irradiating rings and 4 days than one day after the irradiation. A surprising finding observed in some of the examined animals was more intensive neuronal damage after treatment with MK-801. Another unpredicted discovery was intensive morphological alterations found in CA4 and CA3 hippocampal sectors. Moreover, these alterations were not limited to the damaged hemisphere, but were also observed contralaterally. In some of the rats, ischaemic and necrotic cells were additionally found within both parasagittal areas. We connect this atypical localization of the ischaemic changes with dispersion of light emitted by the used lamp. Dispersed light also leads to thrombotic occlusion of the meningeal arteries in the parasagittal area. Among these arteries, thrombosis in pericallosal and penetrating arteries was present. Our experiment demonstrated that if a non-laser lamp is used, brain areas distant from the necrotic ring must be carefully investigated.